FORMATION OF EMOTIONAL RESPONSIVENESS IN CHILDREN OF PRIMARY SCHOOL AGE IN THE LESSONS OF LITERARY READING - Сейтбаева Гульхумар Бахадыр-кызы (European Science Publishing, 2023)
The article describes the characteristics of emotional responsiveness of younger schoolchildren in the lessons of literary reading. Various approaches to the definition of the concepts of "emotion", "emotional responsiveness", as well as methods of forming emotional responsiveness in the lessons of literary reading in primary school are considered.
Keywords: emotions, younger schoolchildren, literary reading, emotional responsiveness, formation.